DMMU Mobile App User Manual - Akshatha, Annaiah (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
DMMU Mobile App User Manual. The mobile app is used to collect real time data on climate harzards such as floods, droughts etc.